MAJAS DALAM AL-QUR’AN (KAJIAN TERHADAP AL-QUR’AN TERJEMAHAN JUZ 30) - Atmawati, Dwi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
The language of the Quran raises specified senses to its readers, such as sense of peacefulness and serenity. Even though the readers read it repeatedly, they or their listeners have never been bored. Furthermore, they can feel the beauty of the holy verses recitation. Because of that, the writer examines the beauty of 30th juz of the Quran in Indonesian by studying the use of tropes. The study focuses on the tropes because they imply a politeness and a beauty of language. This study uses stylistics theory and structural method to analyze the data. In collecting data, the writer notes its verses. The result of study shows that the Quran uses parallelism, imagery, metaphor, euphemism, repetition, personification, tautology, antithesis, antonomasia, rhetorical, and enumeration. Moreover, the writer finds that the most numerous type of trope is parallelism. From the 37 surahs of the 30th juz, 36 surahs contain the tropes. There is only Surah Al-Qadr that does not use the tropes.